The Indonesian Government's Policies to Improve Air Travel Consumer Protection - Arthur Hedar, Harris (Asian Journal of Social and Humanities, 2023)
This research focuses on the conformity of Indonesian policies with international standards and the effectiveness of these policies in improving consumer protection. A comparative analysis involving Indonesia, Malaysia, and Thailand revealed similarities in the issuance of consumer protection laws in 1999, highlighting differences in mechanisms and approaches. The study discusses differences in consumer treatment during flight delays or cancellations, referring to international standards set by IATA and ICAO. Recommendations involve harmonization of policies in ASEAN, implementation of international recommendations, analysis of the role of authorities such as National Dispute Resolution Bodies, strengthening stakeholder engagement for a robust safety culture, increased consumer awareness, and regional cooperation for effective consumer protection policies. The conclusion of this study shows that there is still potential to improve coordination and harmonization between countries in Southeast Asia so that aviation consumer protection can be more effective and equitable throughout the region. These measures will support the understanding and protection of aviation consumer rights consistently, in accordance with the demands of international standards and best practices in the global aviation industry.